An online stigma reduction education program for healthcare workers working with people who inject drugs: Development - Sandy Ezepue; Afolasade Fakolade; Tim O’Shea; Setareh Ghahari (PLoS ONE, 2026)
Canada has a high prevalence of people who inject drugs (PWID), many of whom experience limited access to necessary diagnosis, treatment, and support. PWID often avoid seeking care due to stigma from healthcare workers (HCWs). Implementing a stigma reduction education program for HCWs could improve healthcare outcomes for PWID by fostering compassionate, evidence-based approaches to care, enabling HCWs to overcome biases and deliver non-judgmental care. The objective of this study is to determine the content and format for the development of an online stigma reduction education program for HCWs working with PWID. To accomplish that, we completed interviews with PWID and focus groups with HCWs to obtain input about the content and format for the development of an online stigma reduction education program. PWID provided input on the content of the education program, highlighting the importance of module topics through personal accounts of encountering judgment and discrimination in healthcare settings, which led to their reluctance to seek available services due to fear of stigma. HCWs who participated in the focus groups provided input on the content and reached a consensus regarding the format to inform the program development. Through feedback, participants contributed to shaping the content and format, informing the development of a stigma reduction education program. These findings supported the development and refinement of a program prototype to guide future feasibility and effectiveness evaluations.